Happiness and the meaning of life, a humanistic perspective - Sánchez Jiménez, Hugo Manuel (2023)
The present article sustains the importance and validity that have both the meaning of life, as a central concept of logotherapy and happiness, as an emerging topic of the positive psychology in the social scenary of COVID-19. Since these constructs can be linked in the fields of clinic and social psychology, it is necessary to provide a revision of their theoretical foundations withempiric evidences to clarify its characteristics and divergencies to the scientific community. This process is essential because the existential void, a widespread and visible phenomenon in our society, can be seen as a behavior with the loss of personal values and the emergence of inauthenticity. Therefore, the pursuit of pleasurable emotions has become a reason for beinghappy.